2023
DOI: 10.3390/life13030604
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Pre-mRNA Splicing: Indispensable Role of Post-Translational Modifications of Splicing Factors

Abstract: Pre-mRNA splicing is a process used by eukaryotic cells to generate messenger RNAs that can be translated into proteins. During splicing, the non-coding regions of the RNAs (introns) are removed from pre-mRNAs and the coding regions (exons) are joined together, resulting in mature mRNAs. The particular steps of splicing are executed by the multimegadalton complex called a spliceosome. This complex is composed of small nuclear ribonucleoproteins, various splicing factors, and other regulatory and auxiliary prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 331 publications
0
9
0
Order By: Relevance
“…Yet, despite the limitation in individual PTM annotation, larger patterns between splicing and PTM-driven regulation still emerge. It has previously been suggested that transcription and alternative splicing are functionally coupled [46], and the activity of many splicing factors are regulated by post-translational modifications to induce splicing changes [47]. Examples of potential signaling-transcription-splicing cross-talk exist throughout literature, such as HRAS-mutant dependent splicing via SRSF proteins in lung cancer [48] and combined control of NF- κ B signaling by splicing and PTMs [49].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, despite the limitation in individual PTM annotation, larger patterns between splicing and PTM-driven regulation still emerge. It has previously been suggested that transcription and alternative splicing are functionally coupled [46], and the activity of many splicing factors are regulated by post-translational modifications to induce splicing changes [47]. Examples of potential signaling-transcription-splicing cross-talk exist throughout literature, such as HRAS-mutant dependent splicing via SRSF proteins in lung cancer [48] and combined control of NF- κ B signaling by splicing and PTMs [49].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, after transcription, mRNA precursors contain introns and exons. Non-coding intronic sequences are excised, and exons are joined by a macromolecular complex-the spliceosome [44]. Following this, ribosomes recognize the codons on mRNA and, with the assistance of the appropriate tRNA molecules, synthesize proteins [45].…”
Section: Discussionmentioning
confidence: 99%
“…The mutant variants engineered in this study could serve in complementation assays of the sr45-1 mutant with both SR45 isoforms using native promoter-driven translational fusions. Moreover, it was shown that acetylation, methylation, SUMOylation, ubiquitylation, or even prolyl cis-trans isomerization can regulate the activity of animal SR proteins and other splicing factors (Slišković et al ., 2022; Kretova et al ., 2023). Therefore, dissecting more precisely each of the SR45 isoform domains and focusing on all types of post-translational modifications would demonstrate the importance of specific residues associated to the molecular function of SR45 and to its physiological responses in the plant.…”
Section: Discussionmentioning
confidence: 99%